Adoption of Electric Vehicles (EV) among millennial through the Diffusion of Innovation (DOI) framework: The role of pro-environmental attitude / Faizah Mashahadi, Razmah Mahmod and Faizah Mohd Sohid - Mashahadi, Faizah; Mahmod, Razmah; Mohd Sohid, Faizah (Universiti Teknologi Mara Selangor, 2023)
To encourage sustainable development, the government is now promoting the usage of electric vehicles (EV). Malaysia's present EV market share is still pitiful, nonetheless. At less than 3% of the market in 2021, the adoption rate is much lower than what has been achieved in nearby nations. As millennials are believed to be more environmentally sensitive than previous generations, this study attempts to find out more about their adoption of electric automobiles. This study, which is based on the Diffusion of Innovation (DOI) theory, suggests that proenvironmental sentiments will moderate the significant influence of relative benefits, complexity, compatibility, observability, and trialability on the adoption of electric vehicles. In practice, this study aims to offer thorough details on variables influencing EV adoption from the viewpoints of millennials to policy makers, researchers, and industry players.